Anthropometric Variables as Mediators of the Association of Changes in Diet and Physical Activity With Inflammatory Profile. (8th March 2021) - Cárdenas-Fuentes, Gabriela; Lassale, Camille; Martínez-González, Miguel Ángel; Grau, María; Salas-Salvadó, Jordi; Corella, Dolores; Serra-Majem, Lluis; Warnberg, Julia; Konieczna, Jadwiga; Estruch, Ramón; Pintó, Xavier; Martínez, J Alfredo; et al.
Abstract: Background: Mechanisms underlying the associations of high levels of physical activity (PA) and adherence to the Mediterranean diet (MedDiet) with a better inflammatory profile remain unclear. Our objective was to assess the mediating role of changes in body mass index (BMI) and waist circumference (WC), as markers of body fat in the association of changes in PA and adherence to the MedDiet, with changes in the inflammatory profile. Method: This study included 489 adults, aged 55–75 years, from the PREDIMED-Plus multicenter lifestyle intervention trial. An inflammatory score was calculated, based on 8 blood biomarkers: high-sensitivity C-reactive protein, interleukin 6, interleukin 8, interleukin 18, monocyte chemo-attractant protein-1, C-peptide, leptin, and regulated on activation, normal T-cell–expressed and secreted chemokine. Biomarkers, levels of PA, score of MedDiet adherence, BMI, and WC were measured at baseline and at 1-year follow-up. Linear regression models were fitted according to the Baron and Kenny framework for mediation analysis. Results: Changes in BMI and WC mediated the association of both changes in PA and changes in the MedDiet adherence with the inflammatory score. Body mass index mediated 26% of the association of changes in total PA with the inflammatory profile, and 27% of the association of changes in the MedDiet, while WC mediated 13% and 12% of these associations, respectively. Conclusion: In older adults at high cardiovascular risk, increasing PA levels and adherence to a MedDiet during 1 year were associated with a lower inflammatory score, which was partly mediated by a reduction in body fat. Clinical Trials Registration Number: International Standard Randomized Controlled Trial Number: ISRCTN89898870; registration date July 24, 2014, retrospectively registered.